Is Robotics the real game changer for Urological cancer care during COVID-19 crisis? - Banerjee, Indraneel; Banerjee, Indrajit; Banerjee, Shantimoy (Nepal Journal of Epidemiology, 2021)
The COVID-19 pandemic has not only led to unprecedented loss of human life and a financial crisis but also has influenced the health care system in a big way. While dealing with this crisis, a non COVID-19 deadly disease like cancer care have been greatly compromised. Robotic surgery has revolutionized management of Urological cancer care in India over last few years. It decreases pain, reduces blood loss, promotes early discharge and may be more cost effective in long term as compared to open surgery. During the ongoing pandemic Robotic surgery can be the real game changer by promoting contactless surgery, utilizing minimal personnel and less instruments in the operating room and encouraging early discharge from the hospital.